A Real Utopia Under What Conditions? The Economic and Social Benefits of Workplace Democracy in Knowledge-Intensive Industries - Young-Hyman, Trevor; Magne, Nathalie; Kruse, Douglas (Organization Science, 2023)
Given consistent evidence of its social benefits but questions about its market viability, this paper examines the conditions under which workplace democracy can be understood as a “real utopia”; a viable form of organization that is both economically productive and socially welfare enhancing. Conceptualizing democratic firms as organizations with formally distributed authority and collectivist norms, we argue that democratic firms will operate more productively in knowledge intensive industries, compared with conventional firms in the same industries, because they give authority to those with relevant knowledge and encourage intrafirm information sharing. Next, focusing on intrafirm wage inequality as a key social welfare outcome, we argue that knowledge-intensive sectors are also settings where the benefits of workplace democracy are likely to be greater. Knowledge intensive industries tend to generate greater intrafirm inequality through the adoption of market-based employment policies and reliance on unique expertise, yet the formal structure and collectivist norms of democratic firms are likely to limit these mechanisms of inequality, generating inequality reductions. We test these hypotheses with longitudinal linked employer-employee data from French cooperatives and conventional firms, including firms that shift organizational structures over time. We find robust support for our hypothesis about economic performance and moderate support for our hypothesis about social performance. Funding: This research has been generously supported by the Berg Center for Ethics, the Katz International Business Center, and the Bill Nobles Fellowship, as well as a public grant overseen by the French National Research Agency (ANR) as part of the “Investissements d’Avenir” program [Reference ANR-10-EQPX-17-Centre d’accès sécurisé aux données]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.1622 .